2021
DOI: 10.1038/s41467-021-23261-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-induced topological phase transition and Majorana edge states in low-dimensional orbital-selective Mott insulators

Abstract: Topological phases of matter are among the most intriguing research directions in Condensed Matter Physics. It is known that superconductivity induced on a topological insulator’s surface can lead to exotic Majorana modes, the main ingredient of many proposed quantum computation schemes. In this context, the iron-based high critical temperature superconductors are a promising platform to host such an exotic phenomenon in real condensed-matter compounds. The Coulomb interaction is commonly believed to be vital … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…when creating a potential Wall), the LDOS(ω = 0, j, t) has peaks at site j = 1 and j = 6 at time t/τ = 6, indicating that the slow transfer of MZM R from j = 12 to j = 6 occurred. At t/τ = 6, we also found that the peak height of the electron-and hole-components of the local density-of-states at j = 6 are almost equal (satisfying one of the characteristic features of MZM, γ i = γ † i ) [26]. The average density n(j, t) takes values close to zero for j ≥ 7, while it is close to 0.5 for j ≤ 6 (inset of Fig.…”
mentioning
confidence: 52%
“…when creating a potential Wall), the LDOS(ω = 0, j, t) has peaks at site j = 1 and j = 6 at time t/τ = 6, indicating that the slow transfer of MZM R from j = 12 to j = 6 occurred. At t/τ = 6, we also found that the peak height of the electron-and hole-components of the local density-of-states at j = 6 are almost equal (satisfying one of the characteristic features of MZM, γ i = γ † i ) [26]. The average density n(j, t) takes values close to zero for j ≥ 7, while it is close to 0.5 for j ≤ 6 (inset of Fig.…”
mentioning
confidence: 52%
“…We solved the above models in one-dimensional geometries using the accurate numerical technique density matrix renormalization group (DMRG) [54,55]. Note that a wide variety of real materials do have dominant one-dimensional geometries in their crystal structure, either chains or ladders, and recent theoretical investigations have unveiled a wide range of exotic phenomena including block, chiral, superconducting, dimerized, alternating, and Majorana states in one dimensional systems [57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Thus, one dimensionality is not restrictive physically, and allows our study to be sufficiently accurate to provide reliable many-body information.…”
Section: Resultsmentioning
confidence: 99%
“…At the boundaries and vortex cores, a topological superconductor harbors Majorana quasiparticles, with potential value in the long-sought area of decoherence-free quantum computing [13][14][15][16][17][18] . Topological superconductivity can be induced, for example, by a Rashba spin-orbit coupling together with a magnetic field [19][20][21][22] , and also by a spatiallymodulated spin texture in proximity to a conventional superconductor [23][24][25][26] . A n th -order topological superconductor in d dimensions hosts (d−n)-dimensional Majorana states 27 .…”
Section: Introductionmentioning
confidence: 99%